WARNA MINYAK SAWIT MENTAH DAN STABILITAS WARNA BERDASARKAN TINGKAT KEMATANGAN BUAH YANG BERASAL DARI KEBUN DENGAN KETINGGIAN 800 MDPL - Ika Ucha Pradifta Rangkuti; Alvin Syahputra (Institut Teknologi Sawit Indonesia (ITSI), 2019)
This study aims to determine the color of crude palm oil in the Marjandi estate with an altitude of800 meters above sea level with a comparison of raw fruit, ripe and over ripe and the stability colorof crude palm oil. The results of the analysis of raw fruit at an altitude of 800 m dpl have the lowestcolor compared to other levels of maturity that is equal to 1.1 (red) and 11 (yellow), and maturefruits have the highest colors 1.7 (red) and 17 (yellow). The decline occurred in ripe fruit in theamount of 1.3 (red) and 13 (yellow) with a percentage decrease of 10%. And the results of theanalysis of crude palm oil at an altitude of 800 masl lower than the average value of 400 - 600 masl,which has a value of 3 for red and 30 for yellow. The better color stability of crude palm oil is thatthe yellow color is lower than the red color